Penerapan Algoritma Apriori pada Sistem Informasi Perpustakaan Sekolah SMK Negeri 1 Siantar - DwiSyari, Risti; Safii, M; Fauzan, M (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The SMK Negeri 1 Siantar School Library is one of the special libraries located at the SMK Negeri 1 Siantar School. Libraries provide various kinds of library materials such as books, lessons, lesson questions, and other vocational books. After the researcher made observations, the problem that often occurred was books that were borrowed and returned books that had a non-strategic layout, so that library visitors who did not know the placement found it difficult to find the books they wanted to borrow. This research uses data mining techniques, namely the Apriori Algorithm, the Apriori Method is a method for looking for patterns of relationships between one or more items in a dataset. The Apriori method can be used for data on borrowing books at the Siantar 1 State Vocational School School Library, where the composition of the library books (B1) X_Press UN 2019 B. Indonesia side by side with books (B4) School of Love is a Great Leader and Teacher, if the composition of the book is (B10) Moral Mulia side by side with book (B1) X_Press UN 2019 B. Indonesia, If the book arrangement (B7) X_Press Mathematics is side by side with the book (B5) Relationer, if the book arrangement (B7) X_Press Mathematics is side by side with the book (B9) Indonesian Wisdom Batak Toba, and if the arrangement of the book (B10) Morals Mulia is side by side with the book (B8) Hati Therapy, the data from these items each met the minimum confidance value of 0,5% or the same as the specified 50%. The result of this research is to help library staff arrange the book layout correctly. It is hoped that this research can provide input to the school